(untitled) (Balneo and PRM Research Journal, 2024)
Multiple sclerosis (MS) is a disease of the young and it is the most common cause of non-traumatic disability in this population. Socioeconomic status – education and employment - are environmental factors that may influence MS genesis and disease course. We aimed to evaluate the impact of education and employment status on cognitive and physical disability in a Romanian cohort of people with multiple sclerosis (pwMS). We analyzed data from 111 pwMS in our clinic. Isaacs set test (IST) and EDSS (Expanded Disability Status Scale) were used to evaluate cognition and physical function. Comparison of means and linear regression were used to characterize the relationship between education, employment and cognitive and physical evaluations. Individuals that fit in the ‘high’ education category were more likely to have higher IST scores compared to those that only finished 8 or 12 years of education. Employed patients had significantly better IST scores. Linear regression showed that education can predict cognitive and physical disability. EDSS scores were significantly lower in the ‘high education’ and employed groups. While the relationship between these factors is not yet fully comprehended, asking simple questions about one’s socioeconomic status could represent useful tools in evaluating and managing pwMS